Impact of hemochromatosis gene mutations on cardiac status in doxorubicin‐treated survivors of childhood high‐risk leukemia. Issue 19 (16th July 2013) - Lipshultz, Steven E.; Lipsitz, Stuart R.; Kutok, Jeffery L.; Miller, Tracie L.; Colan, Steven D.; Neuberg, Donna S.; Stevenson, Kristen E.; Fleming, Mark D.; Sallan, Stephen E.; Franco, Vivian I.; Henkel, Jacqueline M.; Asselin, Barbara L.; et al.
Abstract : BACKGROUND: Doxorubicin is associated with progressive cardiac dysfunction, possibly through the formation of doxorubicin‐iron complexes leading to free‐radical injury. The authors determined the frequency of hemochromatosis (HFE) gene mutations associated with hereditary hemochromatosis and their relationship with doxorubicin‐associated cardiotoxicity in survivors of childhood high‐risk acute lymphoblastic leukemia. METHODS: Peripheral blood was tested for 2 common HFE allelic variants: C282Y and H63D. Serum cardiac troponin‐T (cTnT) and N‐terminal pro‐brain natriuretic peptide (NT‐proBNP), which are biomarkers of cardiac injury and cardiomyopathy, respectively, were assayed during therapy. Left ventricular (LV) structure and function were assessed with echocardiography. RESULTS: A total of 184 patients had DNA results for at least 1 variant, and 167 had DNA results for both: 24% carried H63D and 10% carried C282Y. Heterozygous C282Y genotype was associated with multiple elevations in cTnT concentrations ( P = .039), but not NT‐proBNP. At a median of 2.2 years (range, 1.0 years–3.6 years) after diagnosis, the mean Z ‐scores for LV fractional shortening (−0.71 [standard error (SE), 0.25]; P = .008), mass (−0.84 [SE, 0.17]; P < .001), and end‐systolic (−4.36 [SE, 0.26], P < .001) and end‐diastolic (−0.68 [SE, 0.25]; P = .01) posterior wall thickness were found to be abnormal in children with either allele (n = 32). Noncarriers (n = 63) also were found to have below‐normal LV mass (−0.45 [SE, 0.15]; P = .006) and end‐systolic posterior wall thickness (−4.06 [SE, 0.17]; P < .001). Later follow‐up demonstrated similar results. CONCLUSIONS: Doxorubicin‐associated myocardial injury was associated with C282Y HFE carriers. Although LV mass and wall thickness were found to be abnormally low overall, they were even lower in HFE carriers, who also had reduced LV function. Screening newly diagnosed cancer patients for HFE mutations may identify those at risk for doxorubicin‐induced cardiotoxicity. Cancer 2013;119:3555–3562. . © 2013 American Cancer Society . Abstract : Doxorubicin is associated with progressive cardiac dysfunction, possibly by forming doxorubicin‐iron complexes leading to free‐radical injury. In the current study, doxorubicin‐associated myocardial injury was associated with carriers of the C282Y allele, a common allelic variant of hemochromatosis, among long‐term survivors of childhood high‐risk acute lymphoblastic leukemia.